Respuesta :

Answer:

[tex]x = 1 + \sqrt5, x = 1 - \sqrt5[/tex]

Step-by-step explanation:

Hello!

We can solve the quadratic by using the quadratic formula.

Standard form of a quadratic: [tex]ax^2 + bx + c = 0[/tex]

Quadratic Formula: [tex]x = \frac{-b\pm\sqrt{b^2 - 4ac}}{2a}[/tex]

Given our Equation: [tex]g(x) = x^2 - 2x - 4[/tex]

  • a = 1
  • b = -2
  • c = -4

Plug the values into the equation and solve.

Solve

  • [tex]x = \frac{-b\pm\sqrt{b^2 - 4ac}}{2a}[/tex]
  • [tex]x = \frac{-(-2)\pm\sqrt{(-2)^2 - 4(1)(-4)}}{2(1)}[/tex]
  • [tex]x = \frac{2\pm\sqrt{4 +16}}{2}[/tex]
  • [tex]x = \frac{2\pm\sqrt{20}}{2}[/tex]
  • [tex]x = \frac{2\pm\sqrt{4 * 5}}{2}[/tex]
  • [tex]x = \frac{2\pm(\sqrt4 * \sqrt5)}{2}[/tex]
  • [tex]x = \frac{2\pm2\sqrt5}{2}[/tex]
  • [tex]x = 1 + \sqrt5, x = 1 - \sqrt5[/tex]
ACCESS MORE